Sea level rise and coastal flooding risks in the Gulf of Guinea - Franck Eitel Kemgang Ghomsi; Björn Nyberg; Roshin P. Raj; Antonio Bonaduce; Babatunde J. Abiodun; Ola M. Johannessen (Scientific Reports)
Abstract The Gulf of Guinea (GoG) is highly vulnerable to sea level rise, with projections indicating a significant increase in permanently inundated land by 2100, ranging from 1,458.1 to 4,331.7 km2. This study evaluates the severity of potential coastal inundation in the GoG by comparing sea level rise projections from eight reliable CMIP6 models with historical sea surface height (SSH) data from 1993 to 2015 and current onshore topography. Eight model simulations were selected based on their accuracy in reproducing sea level variability in the Tropical Atlantic and the GoG, and their consistency in reflecting the one-month connection lag between equatorial-driven waves and Kelvin Coastal Trapped Waves (CTWs) along the GoG, critical for predicting regional ocean dynamics. Our findings indicate that this connection lag will remain consistent over time. Under high-emission scenarios, up to 95% of coastal areas could be inundated, potentially displacing 2 million people posing a socio-economic shock, given the region’s low GDP and heavy reliance on fisheries. The loss of cultural heritage and livelihoods further compounds the challenges. These findings emphasize the urgent need for targeted adaptation strategies and robust early warning systems, in line with the UN’s Sustainable Development Goals (SDGs), particularly SDG 13 (Climate Action) and SDG 14 (Life Below Water). This study offers a precise and regionally relevant assessment of future risks, providing a foundation for informed policy interventions to mitigate the impacts of climate change and protect vulnerable communities in the GoG.